Effect of dental finishing instruments on the surface roughness of composite resins as elucidated by atomic force microscopy - Botta, Ana Carolina [UNESP]; Duarte, Sillas; Paulin Filho, Pedro Iris; Gheno, Simoni Maria (Cambridge University Press, 2008)
Roughness increases significantly after finishing procedures. The aim of this study was to assess by the atomic force microscope (AFM) the effect of finishing instruments on the surface roughness of composite resins. A nanofiller composite resin (Filtek Supreme, 3M-F) and a microhybrid composite resin (Point 4, Kerr-P) were selected. The finishing procedures were done with a 30-blade carbide bur (C) and a 30-mu m finishing diamond bur (D). Standardized specimens were produced and divided into six experimental groups (n = 4) according to (1) composite resin, (2) absence of finishing (Mylar matrix-M), and (3) finishing instrument (FM, PM, FC, FD, PC, PD). The mean surface roughness was evaluated by AFM in the contact mode. FM and PM groups were assessed statistically by the Student's T test, and FC, FD, PC, PD groups were submitted to variance analysis (ANOVA), both at 5% significance. The mean surface roughness values, in nanometers, were FM, 23.63 (b); FC, 283.88 (c); FD, 510.55 (d); PM, 12.52 (a); PC, 343.98 (c); PD, 531.64 (d). Microhybrid composite displayed less roughness than nanofiller composite in the absence of finishing procedures. The 30-blade carbide bur produced less roughness compared to the extra fine diamond bur.
Keywords: atomic force microscopy; surface roughness; carbide bur; diamond bur; nanofiller composite resin; microhybrid composite resin; finishing techniques